Gambaran Kebutuhan Psikologis pada Anak dengan Gangguan Emosi dan Perilaku (Tinjauan Kualitatif dengan Art Therapy sebagai Metode Penggalian Data) - Anggaswari, A.A.Ayu Wulan Dwi; Budisetyani, I Gusti Ayu Putu Wulan (Jurnal Psikologi Udayana; Vol 3 No 1 (2016)DO - 10.24843/JPU.2016.v03.i01.p09, 2016)
In the process of child development, Children have needs and it’s has to be filled. One of these needs called psychological needs. Psychological needs are a very important role which can give an impact to the growth and development of physical, cognitive, and socio-emotional. When children are not able to obtain their needs, it would cause adjustment problems and one of the problems is emotional and behavioral disorders. There are so many way to detect children with emotional and behavioral disorders, one of these is art therapy. Art therapy can be used as a communication media for children with emotional and behavioral disorders which have difficulty to express or recognize emotions. The purpose of this study is for knowing the psychological needs of children with emotional and behavioral disorders through interview and observation with art therapy. This qualitative study uses a case study approach. The sampling technique of the study was purposive sampling. Subject in this study was a 12-year-old girl with emotional and behavioral disorders. The data was collected with observation, filed note and interview by using art therapy as a media. The collected data are analyzed according to Cresswell’s theory (2007). Based on the results of data analysis, it was found that there are 23 categories which can be classified into three patterns. These patterns are 1. the causes of children with emotional and behavioral disorders; 2. psychological characteristics; and 3. the psychological needs of children with emotional and behavioral disorders. Keywords: Art therapy, Psychological needs, Child, Emotional and Behavioral Disorders